Hormonal and behavioral characteristics associated with the onset of radiotelemetric-detected estrus - G.C. Lamb; D.P. Hoffman; Y. Kobayashi; Jeffrey S. Stevenson (Kansas Agricultural Experiment Station Research Reports, 1996)
The objective of this study was to examine changes in ovarian steroids in relation to the onset of first standing estrus detected by pressure-sensitive rump-mounted devices (ABS HeatWatch® [HW]). Twenty Holstein heifers were treated with PGF on days 5 to 8 (early) 2a or 12 to 15 (late) of the estrous cycle to induce estrus. The following traits were different (P<.05) in early vs late heifers: serum progesterone before PGF (2.3 vs 5 ± .3 ng/ml); 2a interval from PGF to estrus (HW devices: 42 2a vs 52.4 ± 2.8 hr or visual: 45 vs 57 ± 2.5 hr); interval (40.6 vs 57.8 ± 2.2 hr) from PGF to 2a estradiol-17b (E2) peak concentrations in blood serum (17.7 vs 12.3 ± 1 pg/ml) at estrus; duration of estrous cycle after treatment injection of PGF (20 vs 21.4 ± .2 days); interval 2a from onset of estrus to the peak in E2 (1.4 vs "“5.4 ± 1.8 hr); and E2 peak associated with the first dominant ovarian follicle of the estrous cycle following the treatment injection of PGF (2.2 vs 5.2 ± .6 pg/ml), respectively. 2a Durations of estrus and standing events were similar regardless of when the corpus luteum was regressed during either the early or late luteal phase. When all sexual behavior was evaluated after 41 injections of PGF , the 2a number of standing events (28.1 vs 16.1 ± 3.1) was greater (P<.05) in heifers after early-cycle regression of the corpus luteum. Results indicated that the number of standing events per estrus and concentrations of E2 during estrus were related to the duration of progesterone exposure before a PGF -induced luteolysis. 2a The first standing event of estrus detected by the HW device corresponded closely to the peak in E2 and LH at the onset of estrus.; Dairy Day, 1996, Kansas State University, Manhattan, KS, 1996;
Keywords: Dairy Day; 1996; Kansas Agricultural Experiment Station contribution; no. 97-115-S; Report of progress (Kansas Agricultural Experiment Station and Cooperative Extension Service); 771; Standing Estrus; Hormones; Heifers